2019
DOI: 10.1186/s11671-019-2887-0
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine-Eluting Gastrointestinal Stent Using Reactive Oxygen Species-Sensitive Nanofiber Mats for Inhibition of Cholangiocarcinoma Cells

Abstract: Background The aim of this study is to fabricate drug-eluting gastrointestinal (GI) stent using reactive oxygen species (ROS)-sensitive nanofiber mats for treatment of cholangiocarcinoma (CCA) cell. A ROS-producing agent, piperlongumine (PL)-incorporated nanofiber mats were investigated for drug-eluting stent (DES) application. Methods Selenocystamine-conjugated methoxy poly(ethylene glycol) (MePEG) was conjugated with poly(L-lactide) (PLA) to produce block copolymer (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Based on the fact that oxidative stress is increased in UTIs, we have designed a ROS-sensitive nanoparticulate delivery system of CIP for the treatment of UTI. Since diselenide linkages respond to ROS and can be broken in an oxidative stress environment, diselenide linkages were introduced in the copolymer and ROS-sensitive nanoparticles fabricated [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fact that oxidative stress is increased in UTIs, we have designed a ROS-sensitive nanoparticulate delivery system of CIP for the treatment of UTI. Since diselenide linkages respond to ROS and can be broken in an oxidative stress environment, diselenide linkages were introduced in the copolymer and ROS-sensitive nanoparticles fabricated [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jang et al, reported that nanofiber mats fabricated from ROS-sensitive polymers such as poly(L-lactide) (PLA)-PEG copolymer having diselenide linkages have sensitivity against H 2 O 2 and then released piperlongumine in a ROS-sensitive manner [ 31 ]. They argued that drug release must be also accelerated by piperlongumine since piperlongumine is a ROS-producing agent.…”
Section: Resultsmentioning
confidence: 99%
“…Another study confirmed that it takes about 17 weeks to decompose about 10% of the piperlongumine formulation at pH 4 in 25 °C conditions. Finally, piperlongumine formulated into ROS-sensitive nanofibers was found to suppress the growth of cholangiocarcinoma cells [51].…”
Section: Other Therapeutic Activities Of Piper Amidesmentioning
confidence: 98%
“…Especially, the stimuli-responsive drug delivery systems are promising materials for generating smart wound dressings. These materials, with the ability to tune drug release in response to stimuli of pH [71][72][73][74], temperature [71,75,76], light irradiation [11,75], electric field [77], and oxygen [11,78] hold remarkable promise for wound healing.…”
Section: Drug Loaded Electrospun Wound Dressingsmentioning
confidence: 99%